Analysis of the Factors Influencing the Choice of College for Higher Education - Aggarwal, Deepshikha; Sharma, Deepti (International Journal of Computer Sciences and Engineering, 2018)
The higher education sector in India is witnessing a remarkable growth and there are ample opportunities available to the students in terms of choice of courses and institutions for higher education. The institutes are facing a tough competition amongst each other to attract the maximum number of eligible candidates for higher education courses. This paper examines the influence of different factors affecting the college choice decisions of graduate students going for the MCA (Masters of Computer Application) course at the post graduate level. The most relevant factors that were found to influence the decision are faculty, infrastructure, placement, influence of others, extracurricular activities and online advertising. The purpose of study is to identify the factors and their relative influence on the students’ choice for college enrolment. We have used the Pearson’s Chi-square test to conduct the research as we intended to analyse the level of impact of the different factors on the students for the selection of college for higher education. Experimental results have been obtained with the help of different graphs showing the impact of different influential factors on students coming from different graduate level courses. This research can be helpful in providing a guideline to higher education institutes to formulate their strategy to attract the students by considering the various factors that influence the choice of students for selecting a college for higher education.